A Low Literacy, Multimedia Health Information Technology Intervention to Enhance Patient-Centered Cancer Care in Safety Net Settings Increased Cancer Knowledge in a Randomized Controlled Trial. (21st August 2021) - Peipert, John D.; Lad, Thomas; Khosla, Pam G.; Garcia, Sofia F.; Hahn, Elizabeth A.
We tested whether a low-literacy-friendly, multimedia information and assessment system used in daily clinical practice enhanced patient-centered care and improved patient outcomes. This was a prospective, parallel-group, randomized controlled trial with 2 arms, CancerHelp-Talking Touchscreen (CancerHelp-TT) versus control, among adults with Stage I–III breast or colorectal cancer receiving chemotherapy and/or radiation therapy in safety net settings. Each patient was assessed for outcomes at 4 timepoints: after starting treatment (baseline), during treatment, immediately after treatment, and at follow-up assessment. The primary outcomes were health beliefs, cancer knowledge, self-efficacy, and satisfaction with communication about cancer and its treatments. Health-related quality of life (HRQOL) was a secondary outcome. A total of 129 patients participated in the study (65 intervention and 64 control), and approximately 50% of these completed the study. Patients randomized to receive the CancerHelp-TT program had a significantly larger increase in their cancer knowledge in comparison to those randomized to the control arm (effect size = .48, P = .05). While effect sizes for differences between randomized groups in self-efficacy, health beliefs, HRQOL, and satisfaction with communication were small (.10–.48), there was a consistent trend that participants in the intervention group showed larger increases over time in all outcomes compared to the control group. The CancerHelp-TT software was favorably rated by intervention participants. The CancerHelp-TT program showed promise to increase vulnerable cancer patients' cancer knowledge and adaptive health beliefs and attitudes. However, vulnerable patients may need additional interventional support in settings outside cancer clinics.